A design procedure for “liquid to air” type atomisers based on air and water mixture outflow velocity - Krawczyk Piotr; Badyda Krzysztof (Chemical and Process Engineering)
The paper proposes a procedure which enables to determine selected geometric and operating parameters for twin-fluid liquid-to-air atomisers with internal mixing. The presented approach assumes that in order to ensure proper operation of an atomiser it is necessary to design its structure and flow parameters in such a way so that the flow inside the mixing chamber has a dispersive character. In order to calculate a required exhaust cross-section for the analysed atomiser, conditions within the exhaust plane: pressure, density and outflow velocity were estimated. In order to determine diameter and number of orifices supplying the liquid to the mixing chamber of the investigated atomiser type, a multi-parameter analysis based on numerical fluid mechanics was performed. The final part of the paper presents selected results obtained from experimental stand measurements made on an atomiser designed according to the presented procedure.